2016
DOI: 10.1074/jbc.m115.707950
|View full text |Cite
|
Sign up to set email alerts
|

The Cataract-linked Mutant Connexin50D47A Causes Endoplasmic Reticulum Stress in Mouse Lenses

Abstract: Mice expressing connexin50D47A (Cx50D47A) exhibit nuclear cataracts and impaired differentiation. Cx50D47A does not traffic properly, and homozygous mutant lenses show increased levels of the stress-responsive ␣B-crystallins. Therefore, we assessed whether expression of Cx50D47A led to endoplasmic reticulum (ER) stress in the lens in vivo. Although pharmacologic induction of ER stress can be transduced by three different pathways, we found no evidence for activation of the IRE1␣ or ATF6 pathways in Cx50D47A-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…In Cx50G22R or Cx50S50P mutant mice, the IRE1α-XBP1 pathway is activated, while PERK-eIF2α-ATF4 and ATF6α pathways are largely unaffected [96]. In contrast, in Cx50D47A mutant mice, the PERK-eIF2α-ATF4 pathway is activated, while the IRE1α-XBP1 and ATF6α pathways are not activated [97].…”
Section: Connexins and Er Stressmentioning
confidence: 87%
See 1 more Smart Citation
“…In Cx50G22R or Cx50S50P mutant mice, the IRE1α-XBP1 pathway is activated, while PERK-eIF2α-ATF4 and ATF6α pathways are largely unaffected [96]. In contrast, in Cx50D47A mutant mice, the PERK-eIF2α-ATF4 pathway is activated, while the IRE1α-XBP1 and ATF6α pathways are not activated [97].…”
Section: Connexins and Er Stressmentioning
confidence: 87%
“…For example, skin-disease-associated Cx31 mutants were shown to induce all three UPR pathways in transfected cells [95]. ER stress is also activated in cataract-associated Cx50 mutant mouse lenses [96,97]. Interestingly, different UPR pathways are activated by different Cx50 mutations.…”
Section: Connexins and Er Stressmentioning
confidence: 99%
“…The Cx50-D47A, Cx50-G22R, and Cx50-S50P mutations have improper and reduced gap junction communication in the lens and have been implicated in inducing stress pathways or promoting calcium elevation and deposits. 17,25,26 Increased ER stress is also involved in the cell death in skin disease-associated Cx31 mutations. 32,33 However, our data indicate that the BiP expression is not significantly increased, and there is no obvious accumulation of Cx50-R205 mutant proteins in cultured Cx50(R205G/R205G) LECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Cx50-S50P, Cx50-G22R, and Cx50-D47A mutations can increase ER stress. 25,26 We examined the expression of BiP, an ER protein whose increased expression can reflect the activation of unfolded protein response, to test whether ER stress is a possible underlying mechanism for the severe cataracts caused by the Cx50-R205G mutation. Immunostaining of BiP was performed in primary cultured LECs (Fig.…”
Section: Mutant Cx50-r205g Alters Gap Junctions Composed By Cx46 Cx5mentioning
confidence: 99%
“…There are several experimental nuclear cataract models describing the involvement of UPR in the disease pathology, and none of them provided the detailed mechanism. Thus, one can suggest that various ER stressors with different potential and exposure durations may affect the development of the different types of cataracts (Berthoud et al, 2016; Lyu et al, 2016; Mulhern et al, 2006; Palsamy et al, 2014b). Recently, it has been demonstrated the activation of the UPR through discrete pathways in the lens of age- related, high myopia-related and congenital cataracts (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%